Efeitos do tabagismo nos parâmetros seminais - Rúbio, E. M. [UNESP]; Balasteghin, K. T. [UNESP]; Kawano, Paulo Roberto [UNESP]; Barros, J. A T [UNESP]; Pontes, Anaglória [UNESP]; Padovani, Carlos Roberto [UNESP]; Amaro, João Luiz [UNESP] (My University, 2002)
Objectives: We performed a study to evaluate the adverse effects of smoker patient on semen parameters. Material and Methods: We studied retrospective 238 semen specimen, 115 from men smoking and 123 from men nosmoking. Sperm concentration, motility, morphology and vitality were confront in statistic test. Results: In 31% smoke between 1 and 10 cigarettes per day, 26% smoked 10 and 19 per day, 42% smoke more than 20 per day. The distribution of heavy smokes and light smokes did not differ statistically between the groups. Only a significant difference found between smoker and controls, there was about motility, morphology. There is difference in vitality and concentration per ml. Conclusions: This study indicates only a minor effect of smoker patient on male subfertility. Although smokers as a group may not experience reduced fertility, men with marginal semen quality may benefit from quitting smoking.
Effects of cigarette smoking on semen parameters
Keywords: Infertility; Smoke; Sperm; cigarette smoke; adult; cigarette smoking; controlled study; human; major clinical study; male; semen analysis; smoking; smoking habit; sperm; spermatozoon abnormality; spermatozoon capacitation; spermatozoon density; spermatozoon migration; spermatozoon motility; statistical analysis; subfertility